Comparação da gonioscopia com a morfometria do segmento anterior pela fotografia de Scheimpflug - Alonso, Ruiz Simonato (2006)
Purpose: To assess the correlation of noncontact morphometry with anterior chamber tomography (HR Pentacam®) using optical Scheimpflug images compared with current clinical parameters and traditional gonioscopic method with Goldmann lens for evaluating the anterior chamber angle. Method: The Prospective observational study included 112 eyes, 74 (66,07%) eyes of patients classified as open-angle and 38 (33,93%) eyes of patients classified as narrow-angle classified in Shaffer gonioscopic grade. Anterior chamber angle (ACA), anterior chamber volume (ACV) and anterior chamber depth (ACD) were calculated with HR Pentacam and were compared and correlated with clinical parameters of gonioscopy to detect occludable angles. Results: Noncontact morphometry with Scheimpflug images revealed ACA mean 39,20 degrees (0) ± 5,31 for open-angle and 21,18 degrees (0) ± 7,98 for narrowangle. There was a moderate agreement (Kappa test 0,513, p<0.001) between methods considering clinical parameters of open-angle and narrow-angle. ACV and ACD values demonstrated a statistically significant difference comparing open-angle and narrow-angle groups classified in Shaffer Grade and Pentacam; 193 ± 36 mm3 ACV for open-angle and 90 ± 25 mm3 ACV for narrow-angle (p<0.0001) and 3,09 ± 0,42 mm ACD for open-angle and 1,55 ± 0,64 mm ACD for narrow-angle (p<0.0001). Conclusions: There was a strong correlation between anterior chamber volume and anterior chamber depth to detect narrow angles with occludable potential. Moderate statistical correlation was observed for morphometry using HR Pentacam® and Shaffer gonioscopy grade. The most likely explanation for these results is that Pentacam software systematically superimposes ACA compared with traditional gonioscopic method.